Potency of Cockroaches (Periplaneta americana and Blattella germanica) as Vector of Salmonellosis on Ships in Baubau Port - Adi Supryatno; Sri Murtini; Upik Kesumawati Hadi (Hasanuddin University, 2018)
ABSTRACT Cockroaches are insects that act as mechanical vectors of pathogenic agents to humans such as Salmonella sp. The aim of this study was to identify the presence of Salmonella sp. in cockroach bodies on cargo and passenger ships. This research was conducted at Baubau Port from October to December 2017. A total of 24 ships were examined consisting of 12 passenger ships and 12 cargo ships. Cockroaches were collected from rooms inside each ship namely galley, bridge, deck and bathroom. A total of 3 196 cockroaches caught consisting of Periplaneta americana (69.50%), Blattella germanica (29.60%), Periplaneta brunnea (0.66%), Pseudophorapsis sp. (0.03%), Pycnoscelus surinamensis (0.03%), Periplaneta australasiae (0.03%), and Neuphoeta cinerea (0.03%). The presence of Salmonella sp. were examined for cockroach species with a large number of population, namely Periplaneta americana and Blattella germanica. A total of 95.3% of the 42 cockroaches examined in the laboratory contained Salmonella sp.. Based on this research it can be concluded that the cockroaches collected from the ships leaning at Baubau Port can serve as a vector of salmonellosis for both ship crew and passengers. Keywords: Cockroaches, Ships, Salmonella sp, Salmonellosis